1999
DOI: 10.1093/fampra/16.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted telephone interview (CATI) in primary care

Abstract: The CATI-method is a useful tool in screening of high-CVD-risk patients and in guiding them to local CVD primary prevention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 8 publications
0
28
0
3
Order By: Relevance
“…This is an interactive front-end computer system designed to help interviewers to ask questions over the phone, and to record and organize the responses (Ketola and Klockars, 1999). The system is capable of adjusting a pre-defined questionnaire based on the answers obtained and on information about the individual interviewees.…”
Section: The Surveysmentioning
confidence: 99%
“…This is an interactive front-end computer system designed to help interviewers to ask questions over the phone, and to record and organize the responses (Ketola and Klockars, 1999). The system is capable of adjusting a pre-defined questionnaire based on the answers obtained and on information about the individual interviewees.…”
Section: The Surveysmentioning
confidence: 99%
“…Another advantage is the use of a proven methodology (16,27). The biggest limitation of this study is its cross-sectional design, which does not allow us to detect the actual age differences.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on this topic have mainly addressed specific population, such as middleaged women (3,(13)(14)(15)(16), adolescents and younger people (17,18) and older patients (19). Other studies have reported overall prevalence of individual symptoms (5,6,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…computer assisted telephone interviewing), ki je dobro uveljavljena metoda pri preučevanju življenjskih navad ljudi in njihovih zdravstvenih značilnosti (17)(18)(19). Anketiranje poteka prek telefonskega pogovora, med tem pa izpraševalec odgovore sproti zapisuje v računalniški sistem.…”
Section: Postopek Anketiranjaunclassified
“…Prednost predstavlja tudi uporaba metode CATI, ki je uveljavljen način zbiranja podatkov s področja zdravja in zdravstvenih navad prebivalstva (18,19). Omogoča visoko stopnjo odzivnosti (19), nizke stroške anketiranja (18) in enako kakovost zbranih podatkov v primerjavi z anketiranjem v živo (19).…”
Section: Prednosti In Slabosti Raziskaveunclassified